2023
DOI: 10.1111/ejn.16155
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of cellular disruptions in autism spectrum disorder comorbidities

Aoife Griffin,
Mei Chen,
Vijay K. Tiwari

Abstract: Up to 80% of children with autism spectrum disorder have at least one other neuropsychiatric comorbidity. The causes of such disorders are highly genetic, yet many studies fail to take analysis further than risk gene discovery to see cellular and mechanistic changes occurring. Therefore, the goal of this study was to unveil novel gene expression signatures involved in important neurodevelopmental processes that, when disrupted, lead to each of the autism comorbidities of interest. We achieved this by analysing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(35 reference statements)
0
1
0
Order By: Relevance
“… 48 Furthermore, differences in microglial number, activation, and maturation during development drive sexual differentiation in the brain and are observed across brain disorders and diseases. 49 , 50 , 51 , 52 , 53 In humans, we also found that male-biased genes were enriched for neuronal markers (OR = 23.07, p adj < 0.001) ( Table S8 ) and SPVs for neurons were higher in males ( p adj = 0.004) ( Figure 3 D, and Table S9 ). These results are consistent with (1) reports of male-biased neuronal proportions in humans 54 , 55 and (2) our finding that human-macaque conserved male-biased genes (LMM p adj < 0.05 and mashr β > 0; n = 3,922 genes; STAR Methods ) were enriched for synaptic functions ( g:Profiler p adj < 0.05) ( Figure 3 F; Tables S10 – S12 ).…”
Section: Resultsmentioning
confidence: 59%
“… 48 Furthermore, differences in microglial number, activation, and maturation during development drive sexual differentiation in the brain and are observed across brain disorders and diseases. 49 , 50 , 51 , 52 , 53 In humans, we also found that male-biased genes were enriched for neuronal markers (OR = 23.07, p adj < 0.001) ( Table S8 ) and SPVs for neurons were higher in males ( p adj = 0.004) ( Figure 3 D, and Table S9 ). These results are consistent with (1) reports of male-biased neuronal proportions in humans 54 , 55 and (2) our finding that human-macaque conserved male-biased genes (LMM p adj < 0.05 and mashr β > 0; n = 3,922 genes; STAR Methods ) were enriched for synaptic functions ( g:Profiler p adj < 0.05) ( Figure 3 F; Tables S10 – S12 ).…”
Section: Resultsmentioning
confidence: 59%